Variabel-Variabel Yang Berpengaruh Terhadap Penyaluran Kredit Modal Kerja UMKM Di Bali Periode 2002.I-2013.I - Pratiwi, Ida Ayu Meisthya; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 3, Maret 2014 (pp. 76 - 123), 2014)
Banking plays a quite important to the micro sectors in Bali. This study is focused on the influence of non performing loan (NPL), GDRP Bali, uncertainty of  macroeconomics, and global crisis to the distribution of working micro sectors` capital credit by public banks in Bali in 2002.I-2013.I, and used regression linier analysis. The result of this study shown that NPL, GDRP,  uncertainty of macroeconomics, and global crisis had significant effect simultaniously to the distribution of working micro sector`s capital credit. On the other side, in partially, NPL had negatif and significant effect to the distribution  of working micro sector`s capital credit, and GDRP had positive and significant effect to the distribution of working micro sector`s capital credit. Uncertainty of macroeconomics and global crisis are not significant to the distribution  of working micro sector`s capital credit in Bali during 2002.I-2013.I.
Keywords: The Distribution of Working Micro Sector`s Capital Credit; Non Performing Loan (NPL); GDRP Bali; Uncertainty of Macroeconomics; Global Crisis